Glecaprevir/pibrentasvir in patients with chronic HCV and recent drug use: An integrated analysis of 7 phase III studies. (1st January 2019) - Foster, Graham R.; Dore, Gregory J.; Wang, Stanley; Grebely, Jason; Sherman, Kenneth E.; Baumgarten, Axel; Conway, Brian; Jackson, Daniel; Asselah, Tarik; Gschwantler, Michael; Tomasiewicz, Krzysztof; Aguilar, Humberto; et al.
Highlights: Glecaprevir/pibrentasvir (G/P) achieved high SVR12 rates (93%) in recent drug users with chronic HCV infection. Treatment adherence and completion were high (≥96%) regardless of drug use status. G/P was well-tolerated, irrespective of drug use status. Abstract: Background: Injection drug use is the primary mode of transmission for hepatitis C virus (HCV), and treatment guidelines recommend treating HCV-infected people who use drugs; however, concerns about adherence, effectiveness, and reinfection have impeded treatment uptake. Methods: Data were pooled from seven phase III trials that evaluated the efficacy and safety of 8 or 12 weeks of glecaprevir/pibrentasvir (G/P) in patients chronically infected with HCV genotypes 1–6. Patients had compensated liver disease, with or without cirrhosis, and were HCV treatment-naïve or -experienced with interferon or pegylated interferon ± ribavirin, or sofosbuvir plus ribavirin ± pegylated interferon. Patients were grouped into recent drug users (injection drug use ≤12 months before screening, positive urine drug screen [UDS], and/or drug-related adverse event), former drug users (>12 months before screening and negative UDS), or non-drug users. Assessments included sustained virologic response at 12 weeks posttreatment (SVR12), treatment adherence, and safety. Results: Among 1819 patients, 5%, 34%, and 61% were recent, former, and non-drug users, respectively. Treatment adherence and completion were high (≥96%) regardless of drug use status. SVR12 was achieved by 93% (n/N = 91/98), 97% (n/N = 591/610), and >99% (n/N = 1106/1111) of recent, former, and non-drug users, respectively (intention-to-treat analysis). The overall rates of virologic failure were ≤1.5% across all three subpopulations, with no HCV reinfections among recent drug users. Drug-related serious adverse events and adverse events leading to treatment discontinuation were experienced by ≤1% of patients. Conclusions: G/P is a well-tolerated and efficacious pangenotypic regimen for chronic HCV-infected people with recent or active drug use.